Political Stability, Corruption, and Economic Development: Evidence from WAMZ Countries - Hayewa, SuleYa’u; O. Olateju, Adijat (MultiTech Publisher, 2024)
This paper examines the political stability, corruption, and economic progress of the nations that make up the West African Monetary Zone (WAMZ) between 2000 and 2020. To prevent misspecification bias and therefore skewed statistical results, the common features of the panel data were examined first. First of all, the CD test did not find any evidence of cross-sectional dependency across the nations, validating the use of the conventional panel unit root, which does not account for cross-sectional dependence. According to Levin et al. (2002)'s panel unit root test, the variables are integrated of order zero, or I (0).Using the panel VAR framework as a basis, the paper investigates. Emotional intelligence data demonstrated that while corruption impedes regional economic growth, political stability and the rule of law foster it. According to the findings of variance decomposition, the factors under investigation either support or impede the WAMZ countries' economic development. Based on the results the paper recommends that, transparency and accountability at all level of government affairs as well as respecting the constitution in these nations should be preserved in order to overcome all social and political injustice among the countries under study.